JavaServer pages - Bergsten, Hans (O'Reilly, 2002)
Since its inception in 1999, Enterprise Java has taken the Java programming community by storm--developers have realized its potential for building distributed applications. Today, JavaServer Pages (JSP) continues to harmonize how web designers and programmers create dynamic web sites. JSP builds on the popular Java servlet technology and makes it easier to develop dynamic web applications--even if you're not a hard-core programmer. JavaServer Pages, 2nd Edition is completely revised and updated to cover the substantial changes in the 1.2 version of the JSP specification, and also includes detailed coverage of the new JSP Standard Tag Library (JSTL)--an eagerly anticipated specification of a set of JSP elements for the tasks needed in most JSP applications. This book starts off by illustrating how JSP capitalizes on the power of Java servlets to create effective, portable web applications. It shows how to get started using the Apache Tomcat server, and provides detailed coverage of JSP syntax and features, error handling and debugging, authentication and personalization, and how to use JSTL for database access, XML processing, and internationalization. JavaServer Pages recognizes the different needs of the two groups of professionals who want to learn JSP: page authors interested in using JSP elements in web pages, and programmers concerned with learning the JSP API and using JSP effectively in an enterprise application. If you're in the latter group, this book also teaches you such advanced topics as integrating servlets and JavaBeans with JSP, using the popular Apache Struts MVC framework to illustrate how it's done. Finally, the author presents how to develop custom tag libraries, using realistic examples that you can use as a springboard for your own JSP libraries. "This is a complete, comprehensive, and most of all, practical book. The author excels at sharing his vast expertise so web developers can make the most out of JavaServer Pages and related web technologies."--Pierre Delisle, JSP Standard Tag Library Specification Lead